Hubungan Tingkat Pengetahuan, Pendapatan Orang Tua dan Pola Makan dengan Status Gizi Balita di Puskesmas Katobu Kabupaten Muna - Amiruddin, Amiruddin; Samai, Suarna; Munir, Asmawati; Sriwulandari, Ulan (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Nutritional status is the state of children’s health which is determined by the degree of physical need for energy and other nutrients obtained from food and food whose physical impact is measured by anthropometry and categorized based on world health organization standards. This study aims to determine the relationship between diet, level of knowledge and income of parents with nutritional status. This type of research is correlational with a design cross sectional where the population is 1484 respondents, with a sample size of 315 respondents with a proportional cluster random sampling technique. The results showed that there were 39 toddlers (12.4%) in good category eating patterns, 144 toddlers (45.7%) and less than 132 toddlers (41.9%). The level of knowledge of parents in the high category was 47 respondents (14.9%), medium was 244 respondents (77.5%) and low was 24 respondents (7.6%). The income of parents in the high category was 45 respondents (14.3%), 246 respondents (78.1%) medium and low 24 respondents (7.6%). There are 4 under fives (1.3%) over nutrition status, normal 259 toddlers (82.2%) and low 52 toddlers (16.5%). Based on the results of the Spearman Correlation test, it can be concluded that diet, the level of knowledge and income of parents are related to the nutritional status of children under five at the Katobu Health Center, Muna Regency (p < 0.05).